Knowledge, attitude and practice of contraception among nursing and para-medical staff in a tertiary care hospital of Mathura, Uttar Pradesh, India - Garg, Parul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of this study was to study the knowledge, attitude and practice of contraception among nursing and para-medical staff in a tertiary care hospital and also to identify factors that are associated with non-usage of contraception. Methods: The study was conducted on 100 nursing and paramedical staff working at K. D. Medical College and associated hospital at Mathura from November 2019 to January 2020. After obtaining consent, randomly selected married nursing and paramedical staff were given a pre-designed, structured questionnaire on socio-demographic variables, knowledge, attitude and practice towards contraception. Results: In the present study, out of 100 participants, 89 had awareness of contraception. Majority of them knew about condoms, followed by Copper-T/multiload and OCPs. The knowledge about contraception was mainly obtained through social media and health professionals. Conclusions: Health care providers should be equipped with recent information on all the available family planning methods through intensive in-service trainings, seminars/conferences, etc. This will get them informed and all misconceptions will be erased and in turn each health care provider will be able to make informed choice from the various options of family planning methods and practice the best suitable method.